Analysis of the Kampung Family Planning (KB) Program Pucangsawit Village, Jebres District and Sondakan Village, Laweyan District, Surakarta City - Dhiani Nur Fa’izah; Priyono Priyono (International Journal for Disaster and Development Interface, 2023)
Population growth is one of the social problems, in dealing with population growth the governmenthas a Family Planning Program (KB) . This program aims to improve public welfare and health,reduce birth rates, raise the nation's standard of living, and reduce mortality rates in pregnant womenand infants. In its implementation, the government forms the KB Village Program which is located atthe village level area. The research was conducted in KB Pucangsawit Village and KB SondakanVillage. This area was chosen based on the consideration of population growth which increases everyyear so that it needs to be studied in the implementation of the Kampung KB Program. The purpose ofthis study was to analyze the implementation of the Kampung KB program in the two regions and toanalyze the supporting and inhibiting factors found in the implementation of the Kampung KBProgram. This study uses a survey method and uses descriptive, quantitative and SWOT analysis.From the research it shows that the Kampung KB Pucangsawit has an optimal classification while theKampung KB Sondakan has a less than optimal classification. While the education factor af ects theimplementation of the Kampung KB Program 97.69%: 92.11%, then the influence of income is52.15%: 30.20%. The SWOT analysis shows the results of quadrant 1 so that there is an SO strategyto use program opportunities, so as to minimize inhibiting factors and maximize supporting factors.